Multiclass endocrine disrupting compounds in surface water from Selangor river Basin: occurrence and ecological risk assessment - Mohd Zaki, Muhammad Rozaimi; Razak, Muhammad Raznisyafiq; Mohamad Haron, Didi Erwandi; Mohd Isa, Noorain; Md Yusoff, Fatimah; Aris, Ahmad Zaharin (American Chemical Society, 2025)
Endocrine disrupting compounds (EDCs) are emerging environmental pollutants that cause detrimental effects on aquatic organisms and humans despite being present in the environment at trace level. There is insufficient detailed baseline data and ecological risk assessments in river basins globally, despite their ubiquity in freshwater environments. Thus, this study investigated the abundance, distribution, and ecological risks of EDCs in surface water of tropical river basin, using the combination of solid phase extraction and liquid chromatography-tandem mass spectrometry. Approximately, seven EDCs were detected, encompassing bisphenol A (BPA), bisphenol S, bisphenol F (BPF), perfluorooctanesulfonate, perfluorooctanoic acid, 17α-ethynylestradiol (EE2), and 17β-estradiol (E2) in surface water of Selangor River Basin. BPF was observed to be the most prevalent compound at 1098.40 ng/L and was followed by BPA (358.05 ng/L). Human activities, including industrial, commercial, and residential waste discharge into tributaries and lower streams, greatly influence the prevalence of EDCs in the Selangor River Basin. EE2 and E2 had significant ecological risks (risk quotient > 1) and may possess detrimental effects on freshwater organisms. This study addresses the urgent need for baseline data on EDC prevalence and ecological risks for regulatory measures and mitigation strategies to protect aquatic ecosystems.